Relevance of biochar metabolization—evidence from a long-term biochar field experiment - Arthur Gross; Marko Šolić; Bruno Glaser; Tobias Bromm; Snežana Maletić (Frontiers in Sustainable Food Systems)
Biochar soil amendments are a promising strategy for long-term carbon dioxide removal due to their high aromaticity and low decay rate. While complete degradation of biochar was formerly investigated by CO2 measurements and found to be negligible, we are focusing now at potential biochar metabolites. The major constituent of biochar is black carbon (BC), which can slowly be metabolized by microorganisms into benzene polycarboxylic acids (BPCA), so-called black carbon metabolites (BCm). The relevance of this mechanism for the total dissipation of biochar under field conditions remains unknown due to a lack of long-term observations and BCm measurements. This study aimed to quantify BC and BCm in a long-term biochar field experiment covering 11 years in Bayreuth, Germany. Two variants were tested: biochar alone (31.5 Mg ha−1) and a mixture of 31.5 Mg ha−1 biochar with 70 Mg ha−1 compost. Irrespective of the variant, the BC stocks increased threefold following biochar addition to 15–20 Mg C ha−1, and decreased slightly after 11 years in both treatments. BCm stocks were generally low, comprising <3% of total BC. Their content was higher before the application of biochar than afterwards; thus, the addition of biochar did not lead to higher BCm release, but rather the opposite. This result indicates that microorganisms preferentially consume more labile substances introduced with the biochar rather than BC and that microbial diversity may need time to adjust their diet. Thus, BCm release could play a larger role over longer timescales. Considering the total amounts of biochar added to the soil, BCm represents a very small fraction which, for the ecological evaluation of biochar’s dissipation, is negligible.